Penerapan Refleksi Diri dan Self Evaluation Sebagai Keterampilan Dasar Dalam Meningkatkan Profesionalisme Pada Mahasiswa Kedokteran - AS, Nyimas Natasha (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2015)
ABSTRACT The field of medicine and health will continue to alter along with the change and advancement in information and technology. In facing these changes, a doctor should be able to prepare and maintain his/her professionalism in order to keep the trust of patients. A doctor can improve and sustain his/her professionalism by following a program, which is called, Continuing Professional Development (CPD). CPD is defined as the process of lifelong learning for individual or team, that enables medical professionals to expand and develop their potential in managing a high standard of health care and continuously improve the quality of health services to meet the needs of patients. Lifelong learning process should be implemented in medical education, so that medical education graduates can always apply continuously in the health service. Medical educational institutions should be able to teach the skills that are needed build lifelong learning to the students. Self-reflection and self-evaluation learning on medical students are part of the skills that must be possessed by students in implementing the lifelong learning. Â Keywords: Professionalism, lifelong learning, self-reflection, self-evaluation